An Expression of Power, Unity and Faith Through Dance: The /Abine-mfor/ Fon’s Dance of the Bafut People in the Bamenda Grassfields of Cameroon - Tikere Moffor, Exodus; Dieudonne , Nebane; Kum Awah, Paschal (Technium Education and Humanities, 2023)
An Annual festival is a cultural event which is celebrated by most if not all Western Grassfields Fondoms. In Bafut, this annual festival is referred to as ‘abine-mfor’ (fon’s dance) or ‘flutes’ dance’. This occasion was instituted by the very first fon of the Bafut Fondom to commemorate the ancestors and spirits through sacrifices and dancing. The majority of Bafut people admire and celebrate the Abine-mfor with passion but very few understand the raison d’être of the dance. The question is what is the cultural significance of the fon’s dance in the life of the Bafut fondom? This paper examines the symbolism of Abine-mfor and the functions of the ceremony in the life of the fondom. Collecting data for this paper, we used the qualitative method. This method was employed through techniques such as participant observation, in-depth interview, informal discussions, literature review and photography. The data was interpreted using theories of symbolic anthropology of Geertz, and functionalism of Malinowski and Brown. Major findings reveal that in the Annual dance, the villagers perform traditional dances, sacrifices to honour their ancestors and spirits. This ceremony therefore reflects the belief system, social and political form of organisation of the Bafut Fondom. Cultural manifestations such as Abine-mfor and others should be documented (Historical Particularism of Boas) so that Bafut and non-Bafut people should understand its importance to the cultural heritage of Bafut in particular and that of Cameroon in general.